Bone mineral density and body composition after laparoscopic sleeve gastrectomy in men: A short-term longitudinal study - Adamczyk, Piotr; Bužga, Marek; Holéczy, Pavol; Švagera, Zdeněk; Šmajstrla, Vít; Zonča, Pavel; Pluskiewicz, Wojciech (International journal of surgery (London, England), 2015)
INTRODUCTION: Longitudinal changes in bone and body composition occurring in obese men after laparoscopic sleeve gastrectomy (LSG) has been evaluated. METHODS: In short-term longitudinal study, 25 obese men in mean baseline age 44.8 ± 10.9 years and mean body mass index (BMI) 43.3 ± 4.4 kg/m(2)were assessed after undergoing LSG for obesity. Bone mineral density (BMD) (spine, femoral neck [FN], total hip [TH], and total body [TB]) and body composition (TB bone mineral content [BMC], fat, % of fat, lean, lean BMC, total mass) were assessed at baseline, and after three and six months. RESULTS: Mean body measurements, including weight, BMI, waist and hips, decreased significantly over the study period (p < 0.0001). FN BMD (p < 0.01) and TH BMD (p < 0.001) decreased, and spine BMD increased significantly (p < 0.001). TB BMD did not change. Weight decreased by 21.3 ± 7.3%, BMI by 21.2 ± 7.3%, FN BMD by 3.32 ± 6.35%, TH BMD by 3.51 ± 3.95% whereas spine BMD increased by 2.89 ± 5.1%. TB BMC increased by 2.4 ± 4.62%; all other variables relating to body composition decreased: fat by 33.0 ± 9.6%, lean mass by 12.8 ± 6.1%, lean BMC by 12.3 ± 5.9%, total mass by 20.1 ± 6.4%, and % fat by 15.8 ± 7.2%. CONCLUSIONS: After LSG, body size and variables related to body composition (except for TB BMC) decreased with an accompanying decrease in FN BMD in the men in this study. Spine BMD increased, and TB BMD did not change.
Keywords: Calcium; obezita; Anthropometry; antropometrie; gastrektomie; Humans; Longitudinal Studies; laparoskopie; index tělesné hmotnosti; lidé středního věku; Body Mass Index; složení těla; Gastrectomy; Lumbar Vertebrae; vápník; dospělí; lidé; Vitamin D; Weight loss; bederní obratle; Adult; longitudinální studie; Male; Middle Aged; Bone Density; kostní denzita; Body Composition; Laparoscopy; Body composition; Laparoscopic sleeve gastrectomy; Bone mineral density; Obesity; Body Weight; tělesná hmotnost; mužské pohlaví; vitamin D